Insights into how Malaysian adults with limited health literacy self‐manage and live with asthma: A Photovoice qualitative study - Hani Salim; Ingrid Young; Ping Yein Lee; Sazlina Shariff‐Ghazali; Hilary Pinnock; RESPIRE collaboration (Wiley, 2022)
Abstract Background Adjusting to life with a chronic condition is challenging, especially for people with limited health literacy, which is associated with low compliance with self‐management activities and poor clinical outcomes. Objective We explored how people with limited health literacy understand asthma and undertake self‐management practices. Design We adapted the arts‐based qualitative methodology Photovoice. Setting and Participants We sampled ethnically diverse adults with asthma and limited health literacy from four primary healthcare clinics in Malaysia. After a semistructured in‐depth interview, a subset of participants took part in the Photovoice component in which participants undertook a 2‐week photo‐taking activity and subsequent photo‐interview. Interviews, conducted in participants' preferred language, were audio‐recorded, transcribed verbatim, translated and analysed thematically. We used the Sorensen's framework (Domains: access, understand, appraise, apply) to describe participants' experience of living with asthma, what they understood about asthma and how they decided on self‐management practices. Results Twenty‐six participants provided interviews; eight completed the Photovoice activities. Participants with limited health literacy used various sources to access information about asthma and self‐management. Doctor-patient communication had a pivotal role in helping patients understand asthma. The lack of appraisal skills was significant and experiential knowledge influenced how they applied information. Self‐management decisions were influenced by sociocultural norms/practices, stigmatizing experiences, and available social support. Conclusion Locally tailored multilevel interventions (interpersonal, health system, community and policy) will be needed to support people with limited health literacy to live optimally with their asthma in an ethnically diverse population. Patient/Public Contribution Patients were involved in the study design, recruitment, analysis and dissemination.